250 cases in clinic medicine fourth edition - R.R Baliga (saunders elsevier, 2012)
now in its fourth edition, this portable, versatile and practical self-assessment text is designed to help undergraduate and postgraduate candidates pass clinical examination in general internal medicine across the english-speaking world